Trends in incidence, treatment and survival of borderline ovarian tumors in the Netherlands: a nationwide analysis. (3rd July 2019) - Schuurman, Melinda S.; Timmermans, Maite; van Gorp, Toon; de Vijver, Koen K. Van; Kruitwagen, Roy F. P. M.; Lemmens, Valery E. P. P.; van der Aa, Maaike A.
Abstract: Background: Population-based data on borderline ovarian tumors (BOTs) are scarce and information regarding recent trends in incidence, treatment and survival is lacking. The purpose of this study was to analyze these trends in the Netherlands and to assess the risk of developing a subsequent invasive ovarian tumor. Material and methods: All consecutive patients diagnosed with BOTs between 1993 and 2016 ( n  = 7113) were identified from the Netherlands Cancer Registry (NCR). Annual age-adjusted incidence rates were calculated. Relative survival (RS) analyses and multivariable analyses estimating excess mortality were conducted. Patients with a subsequent invasive ovarian tumor were identified by the NCR. Results: Age-adjusted incidence increased from 2.1/100, 000 person-years in 1993 to 4.2/100, 000 in 2011, after 2011 the incidence declined. The proportion of bilateral tumors decreased over time from 16% in 1993–1998 to 11% in 2005–2010 and remained stable onwards. Survival improved over time (excess mortality ratioadjusted 2011–2016 versus 1993–1998: 0.25; 95%CI: 0.13–0.47). Five-year RS increased from 91% in 1993–1998 to 98% in 2011–2016 and 10-year RS from 88% in 1993–1998 to 96% in 2005–2010. Fewer patients were treated with chemotherapy (4.4% in 1993–1998 versus 0.7% in 2011–2016). During a median follow-up time of 8 years, 0.9% developed a subsequent invasive ovarian carcinoma. Conclusions: The incidence of BOTs increased over time from 1993 until 2010 but declined since 2011. This decline may be partly due to changes in the classification of gynecological tumors, as serous BOTs are now more often diagnosed as low grade serous ovarian cancers. Survival is high and has improved since 1993. The risk of a subsequent invasive ovarian carcinoma seems low.